UMP alumni builts the business empire of Caliphs Technology PLT - Nurizzatul Alin, Ahmad Bastani; Siti Nurfarmy, Ibrahim (2020)
Never thought of owning a company. When asked when he was younger, Abang Fairul Syarmil Abang Mohd dreamed of becoming a pilot, but who would have thought that his studies in Computer Science at Universiti Malaysia Pahang (UMP) would allow him the opportunity to build his business empire, Caliphs Technology PLT.